Cognitive Load in Programming Education: Easing the Burden on Beginners with REXX - Winkler, Till; Flatscher, Rony G (Conference proceedings, 2023)
To learn and teach programming is very difficult, often leads to poor results, and causes many students to drop out or turn away from the subject. Cognitive load theory can help to understand the challenges students face, improve programming education, and select an appropriate language for instruction. In this paper, we take a theoretical look at programming education and, in particular, language characteristics that reduce students' cognitive load and thus enable rapid learning and frustration-free productivity. We introduce the REXX language and some of its favorable characteristics that make it possible to teach novices programming within a single semester. In this limited time, students are empowered to program Microsoft products (Windows, Office), address the command line, grasp the basics of objectoriented programming, use Java classes, and create portable graphical user interfaces (GUIs) with JavaFX.